Unincreased risk of hospitalized infection under targeted therapies versus methotrexate in elderly patients with rheumatoid arthritis: a retrospective cohort study - Ryoko Sakai; Eiichi Tanaka; Masako Majima; Masayoshi Harigai (Arthritis Research & Therapy, 2022)
Abstract Background Infection is one of the primary concerns during treatment for rheumatoid arthritis (RA) in elderly patients. However, infection risk of patients with RA receiving targeted therapy (TT) including biological disease-modifying antirheumatic drugs (bDMARDs) and Janus kinase inhibitors (JAKIs) in elderly patients are scarce. The aim of this study was to compare the risk of hospitalized infection (HI) with TT versus methotrexate (MTX) therapy among young, elderly, and older elderly patients with RA. Methods Using Japanese claims data, patients satisfying the following criteria were enrolled: (1) ≥ one ICD10 code for RA; (2) ≥ one prescription of MTX or TT (bDMARDs and JAKIs) between April 2008 and September 2018; and (3) ≥16 years old. We calculated the incidence rate (IR) of HI per 100 patient-years in the young, elderly, and older elderly groups (those aged 16–64, 65–74, and ≥75 years, respectively) and the IR ratio (TT vs. MTX) of HI. A logistic regression model was used to estimate the associations between HI and TT versus MTX in each group. Results The overall IR of HI per 100 patient-years (95% confidence interval) was 3.2 [2.9–3.5], 5.0 [4.6–5.4], and 10.1 [9.5–10.9] in the young, elderly, and older elderly groups, respectively. Concomitant use of MTX or immunosuppressive DMARDs with TT was less frequent in the elderly and older elderly groups. The adjusted odds ratio of TT vs. MTX for HI was 1.3 (1.0–1.7; p = 0.021), 0.79 (0.61–1.0; p = 0.084), and 0.73 (0.56–0.94; p = 0.015) in the young, elderly, and older elderly groups, respectively. Conclusion The overall IR of HI was increased with age. The risk of HI under TT compared to MTX was not elevated in elderly and older elderly patients after adjusting for patients’ characteristics and concomitant treatments.